2008
DOI: 10.1007/s00508-008-1117-z
|View full text |Cite
|
Sign up to set email alerts
|

Prävention der kontrastmittelinduzierten Nephropathie mit isotonem Natriumbikarbonat: eine Meta-Analyse

Abstract: This meta-analysis confirms that, based on currently available randomized trials, bicarbonate therapy is effective in preventing contrast media-induced nephropathy. However, study heterogeneity and publication bias are substantial, and therefore further controlled clinical trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 28 publications
1
33
1
3
Order By: Relevance
“…This is much higher compared to the incidence of RRT in non-ICU patients with CA-AKI, which is generally less than 1% in patients without risk factors and may increase to 4% in patients with underlying chronic kidney disease or patients undergoing primary PCI for acute coronary syndrome [4,15,16]. This high incidence can be explained by the greater severity of illness and resulting higher incidence of AKI in an ICU cohort.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is much higher compared to the incidence of RRT in non-ICU patients with CA-AKI, which is generally less than 1% in patients without risk factors and may increase to 4% in patients with underlying chronic kidney disease or patients undergoing primary PCI for acute coronary syndrome [4,15,16]. This high incidence can be explained by the greater severity of illness and resulting higher incidence of AKI in an ICU cohort.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of CA-AKI ranges between 0 and 50% depending on the case mix and the definition for CA-AKI that is used [1,3,4,14,15]. The most commonly used definition is an increase of serum creatinine C0.5 mg/dL or C25% from baseline, assessed 48-72 h after the procedure [16].…”
Section: Introductionmentioning
confidence: 99%
“…That meta-analysis suggests, but does not confirm, that bicarbonate is effective in preventing CN. 60 Hogan et al, analyzing seven controlled and randomized clinical trials comparing sodium bicarbonate-based hydration with saline-based hydration in 1,307 patients, have found a significant reduction in acute kidney injury associated with the use of contrast medium in patients receiving hydration with sodium bicarbonate [5.96% in the bicarbonate arm versus 17.23% in the saline arm; RR = 0.37 (p = 0.005)]. The authors have concluded that, sodium bicarbonate-based hydration proved to be superior to saline-based hydration for preventing CN.…”
Section: Sodium Bicarbonatementioning
confidence: 99%
“…65 Thus, several meta-analyses have suggested that sodium bicarbonate-based hydration is superior to saline solution in preventing CN, as shown in Table 1. [60][61][62][63][64][65] A recent meta-analysis assessing ten studies has shown conflicting results with the use of N-acetyl cysteine and hydration with sodium bicarbonate * 7 studies ≥ 25%; 2 studies ≥ 0.5 mg/dL; 6 studies ≥ 25% and/or ≥ 0.5 mg/dL. ** most studies.…”
Section: Sodium Bicarbonatementioning
confidence: 99%
See 1 more Smart Citation